Biofuel Production: Harnessing Microalgal Biotechnology for Sustainable Industrial Waste Management - Rai M.; Khan R.; Rai S.; Mesevilhou S.; Singh S.K.; Rai S. (My University, 2025)
The chapter provides a comprehensive overview of microalgal biotechnology for sustainable biofuel production using industrial waste as a nutrient source. It highlights the benefits of microalgal biofuels, such as reduced greenhouse gas emissions and decreased reliance on fossil fuels. The chapter explores high-lipid-productive microalgal species and metabolic pathways to enhance lipid accumulation through genetic engineering. It also covers extraction and conversion processes for transforming microalgal lipids into biodiesel and bioethanol, discussing their advantages and limitations. The economic feasibility and scalability of microalgal biofuel production are critically assessed, along with potential applications beyond biofuels. Future prospects and challenges, including large-scale cultivation, improved strain selection, and efficient downstream processing, are outlined. Multidisciplinary collaborations are emphasized for successful implementation. Overall, this chapter serves as a valuable resource for researchers, industry professionals, and policymakers seeking sustainable and renewable energy solutions. © 2025 Elsevier Inc. All rights reserved.